Conditional probabilities of substance use disorders and associated risk factors: Progression from first use to use disorder on alcohol, cannabis, stimulants, sedatives and opioids. (1st January 2019) - Marel, Christina; Sunderland, Matthew; Mills, Katherine L.; Slade, Tim; Teesson, Maree; Chapman, Cath
Highlights: Pre-existing mental disorders increases the risk of developing SUD. Prior SUD increases the risk of transitioning from use to use disorder. Highest rates of transition to SUD occurred among stimulant and opioid users. Mood and anxiety disorders increased the risk of transitioning to AUD and CUD. The rapidity of transition to SUD emphasizes the narrow opportunity to intervene. Abstract: Background: Relatively little is known about factors that may lead to the development of a substance use disorder (SUD), across a range of drug classes. This study aimed to identify factors that predict the likelihood of transition from use to SUD and the speed with which this may occur at the population level, with a focus on the impact of pre-existing mental disorders. Methods: Data were collected as part of the 2007 Australian National Survey of Mental Health and Wellbeing, a nationally representative survey of 8841 Australian adults. A series of discrete time survival analyses were undertaken on data pertaining to the age of onset of use and symptoms of use disorder, for alcohol, cannabis, sedatives, stimulants, and opioids, as well as the impact of pre-existing mood and anxiety disorders on the likelihood of developing a SUD. Results: Lifetime cumulative probability estimates indicated that 50.4% of stimulant, 46.6% of opioid, 39% of sedative, 37.5% of alcohol, and 34.1% of cannabis users would develop a SUD on those substances, within an estimated 14, 12, 8, 30, and 23 years after onset respectively. Pre-existing mental disorders were significantly associated with increased risk of developing a SUD for alcohol, cannabis and stimulant use disorder. Conclusion: The relative speed associated with the transition from use to SUD emphasizes the narrow window of time available to intervene, underscoring the urgency of early identification of mental health conditions and the timely provision of appropriate evidence-based interventions, which could potentially prevent the development of secondary SUDs.